Die verband tussen leerstrategieë en intelligensie - Harmse, Carel Johannes (2014)
M.Ed. (Educational Psychology) === The object of this research project was to determine if learning strategies of first year students with different intellectual abilities differed and if these differences also applied to male and female students of different language groups. The project comprised of two parts. The first part consisted of a literature study which defined the concepts of intelligence, learning, cognition, metacognition and learning strategies. This was followed by a discussion of possible reasons why intelligent students fail to use effective learning strategies . The second part included an empirical investigation of the differences in the learning strategies of first year students with different intellectual abilities. The students were divided into the following groups: Afrikaans speaking male students, Afrikaans speaking female students, male students from other language groups and female students from other language groups. It was evident from the literature stUdy that learning strategies consist of self-management skills that the learner acquires, presumably over a period of years, to govern his own processes of attending, learning and thinking. Researchers agree that the mastering of learning strategies by a student can influence the success of his university career. When attending university even the intelligent students need effective learning strategies. Some students fail to acquire affective learning strategies while still at school. These students cannot cope with the large quantities of study material and consequently they may underachieve or even fail.